Try taking the partial derivatives and see if you notice anything about them.
Let u = x + y and v = x -y so that x = (u + v)/2 and y = (u-v)/2
Given a twice continuously differentiable functions f(x,y) set
g(u,v) = f( (u+v)/2, (u-v)/2) so that f(x,y) = g( x+y, x-y)
1) Relate ∂f/∂x, ∂f/∂y to ∂g/∂u, ∂g/∂v
2) Relate ∂^2f/∂x^2, ∂^2f/∂y^2 to ∂^2g/∂u^2 , ∂^2g/∂v^2 and ∂^2g/∂u∂v
well the first part I said, using the chain rule
∂g/∂u = ∂g/∂x ∂x/∂u + ∂g/∂y ∂y/∂u = (1/2) ∂f/∂x + (1/2) ∂f/∂y
∂g/∂v = ∂g/∂x ∂x/∂v + ∂g/∂y ∂y/∂∂v = (1/2) ∂f/∂x - (1/2) ∂f/∂y because f(x,y) = g(u,v)
for the second part
∂^2/∂x^2 = ∂/∂x (∂g/∂u ∂u/∂x + ∂g/∂v ∂v/∂x)
where should I go from here?